Severe Ocular Manifestations in Stevens-Johnson syndrome : a case report: Poster Presentation - Case Report - General practitioner - Eric Jansen; Dian Wikaningtyas (Majalah Oftalmologi Indonesia, 2023)
Introduction : Stevens-Johnson syndrome (SJS) is a severe mucocutaneous reactions, characterized by cell death in the epidermis, resulting in blistering and sloughing. Hypersensitivity reaction to drug causes the majority of SJS cases. Ocular involvement occurs in 80% of patients in the acute phase. Case Illustration m A 38-year-old female was consulted to the ophthalmology department with diagnosis of Stevens- Johnson syndrome (SJS). She complained of bilateral eye redness and blurred vision. She was first admitted to the Emergency Department with complaints of burning sensation, progressive rash, and blistering skin all over her body for the past 2 weeks. Ophthalmology examination revealed a visual acuity of no-light perception (NLP) for both eyes. The anterior segment examination in both eyes showed the palpebra was edema and lagophthalmos, conjunctival hyperemia and corneal ulcer, while the posterior segment could not be identified. The patient was hospitalized in the intensive care unit (ICU) due to her symptoms and clinical findings. She was treated with combination of systemic intravenous antibiotics and steroid, eye drops and eye ointment. After 2 weeks, she was able to blink partially. She was discharged after 20 days of intensive treatment. Discussion : Conclusion : Ocular manifestations in SJS are a significant aspect of the disease that can lead to severe visual impairment or even blindness. A multidisciplinary approach to managing SJS is necessary to prevent and treat the ocular manifestations of the disease effectively.